Alantolactone selectively suppresses STAT3 activation and exhibits potent anticancer activity in MDA-MB-231 cells. Issue 1 (1st February 2015) - Chun, Jaemoo; Li, Rui-Juan; Cheng, Mao-Sheng; Kim, Yeong Shik
Highlights: STAT3 is a transcription factor that is a potent regulator of tumorigenesis. Alantolactone suppresses constitutive and inducible STAT3 tyrosine phosphorylation. Alantolactone inhibits NF-κB translocation to the nucleus. Alantolactone inhibits cell migration, invasion, adhesion, and colony formation. Alantolactone inhibits the tumor growth of MDA-MB-231 xenografts in mice. Abstract: The important goal of cancer drug discovery is to develop therapeutic agents that are effective, safe, and affordable. In the present study, we demonstrated that alantolactone, which is a sesquiterpene lactone, has potential activity against triple-negative breast cancer MDA-MB-231 cells by suppressing the signal transducer and activator of transcription 3 (STAT3) signaling pathway. Alantolactone effectively suppressed both constitutive and inducible STAT3 activation at tyrosine 705. Alantolactone decreased STAT3 translocation to the nucleus, its DNA-binding, and STAT3 target gene expression. Alantolactone significantly inhibits STAT3 activation with a marginal effect on MAPKs and on NF-κB transcription; however, this effect is not mediated by inhibiting STAT3 upstream kinases. Although SHP-1, SHP-2, and PTEN, which are protein tyrosine phosphatases (PTPs), were not affected by alantolactone, the treatment with a PTP inhibitor reversed the alantolactone-induced suppression of STAT3 activation, indicating that PTP plays an important role in the action of alantolactone. Finally, alantolactone treatment resulted in the inhibition of migration, invasion, adhesion, and colony formation. The in vivo administration of alantolactone inhibited the growth of human breast xenograft tumors. These results provide preclinical evidence to continue the development of alantolactone as a STAT3 inhibitor and as a potential therapeutic agent against breast cancer.